The effect of two overlapping designs in scheduling their exercises to improve the accuracy of the motor performance of some of the skills of young players in volleyball (Journal of the College of Basic Education, 2022)
Search goal to:1. Preparing an educational curriculum based on the two overlapping designs in scheduling their exercises to suit the abilities of the research sample.2. Identifying the percentages of improvement in the accuracy of the motor performance of some of the skills of the young players in volleyball for the research sample.3. Identify which of the two research designs is more effective in improving the accuracy of the motor performance of some of the skills of the young players in volleyball for the research sample.The researchers used the experimental method in their study, and the research sample consisted of (12) players out of the community, totaling (31) players, representing a percentage of (38.7%) of the total research community, and through drawing lots, the sample was randomly divided into two experimental groups that included each A group of (6) players were distributed into two research designs, that is, each design is represented by one experimental group.